2020
DOI: 10.1094/php-05-20-0038-rs
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield Loss Estimates Due to Diseases in the United States and Ontario, Canada, from 2016 to 2019

Abstract: Annual reductions in corn (Zea mays L.) yield caused by diseases were estimated by university Extension-affiliated plant pathologists in 26 corn-producing states in the United States and in Ontario, Canada, from 2016 through 2019. Estimated loss from each disease varied greatly by state or province and year. Gray leaf spot (caused by Cercospora zeae-maydis Tehon & E.Y. Daniels) caused the greatest estimated yield loss in parts of the northern United States and Ontario in all years except 2019, and Fusarium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…Mueller at al. [ 50 ] reported that weather in the United States in 2018 was characterized by unfavorably wet conditions and delayed harvest which resulted in an estimated 2.5 billion bushels of corn grain contaminated with mycotoxins. Our survey showed frequent mycotoxin contamination of grain and silage in 2018, although 2018 was not necessarily the year with highest mean levels of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Mueller at al. [ 50 ] reported that weather in the United States in 2018 was characterized by unfavorably wet conditions and delayed harvest which resulted in an estimated 2.5 billion bushels of corn grain contaminated with mycotoxins. Our survey showed frequent mycotoxin contamination of grain and silage in 2018, although 2018 was not necessarily the year with highest mean levels of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lobell et al (2011) reported that recent climate change between 1980 and 2008 has already reduced the potential global maize production by about 3.8%, thereby countervailing some of the yield gains from breeding and other technological advances. In addition, maize is increasingly challenged by plant pathogens (Mueller et al, 2020), insect pests (De Groote et al, 2020), and other biotic and abiotic stress factors such as heat and drought (Cairns et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since its emergence in Western Africa in 1949, where it caused yield losses of ~50% 5 , southern rust epiphytotics were responsible for ~80% yield loss in the Philippines 6 , ~45-50% yield loss in the Mississippi Valley in the early 1970s 7 , and ~40-50% yield loss in China in the late 1990s 8 . In contrast, today Southern rust infections infrequently reach economic threshold losses in Texas to justify fungicide treatment 9 because of non-conducive weather. Plant breeders face several challenges in combating southern rust, from expert scores being subject to rater variability 10 , signi cant time commitments required for pathologists to score large elds, to selecting for multiracial pathogen resistant germplasm in which general (horizontal) resistance, often found in tropical germplasm, is favored 11 .…”
Section: Southern Rustmentioning
confidence: 99%